2022
DOI: 10.1121/10.0009238
|View full text |Cite
|
Sign up to set email alerts
|

Predicting synapse counts in living humans by combining computational models with auditory physiology

Abstract: Aging, noise exposure, and ototoxic medications lead to cochlear synapse loss in animal models. As cochlear function is highly conserved across mammalian species, synaptopathy likely occurs in humans as well. Synaptopathy is predicted to result in perceptual deficits including tinnitus, hyperacusis, and difficulty understanding speechin-noise. The lack of a method for diagnosing synaptopathy in living humans hinders studies designed to determine if noise-induced synaptopathy occurs in humans, identify the perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 75 publications
0
14
0
Order By: Relevance
“…The effect of excessive noise exposure on the amplitude of wave I of young normal-hearing human adults has been inconclusive. Some studies have reported that a smaller amplitude of wave I of the ABR is associated with high noise exposure in young subjects (Stamper and Johnson, 2015a,b;Liberman et al, 2016;Bramhall et al, 2017Bramhall et al, , 2021Valderrama et al, 2018;Buran et al, 2022), while several other studies failed to document such an effect (Grinn et al, 2017;Grose et al, 2017;Prendergast et al, 2017aPrendergast et al, , 2018Skoe and Tufts, 2018;Couth et al, 2020). Table 3 shows a summary of studies that investigated the effect of noise exposure on ABR wave I amplitude in humans.…”
Section: Human Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of excessive noise exposure on the amplitude of wave I of young normal-hearing human adults has been inconclusive. Some studies have reported that a smaller amplitude of wave I of the ABR is associated with high noise exposure in young subjects (Stamper and Johnson, 2015a,b;Liberman et al, 2016;Bramhall et al, 2017Bramhall et al, , 2021Valderrama et al, 2018;Buran et al, 2022), while several other studies failed to document such an effect (Grinn et al, 2017;Grose et al, 2017;Prendergast et al, 2017aPrendergast et al, , 2018Skoe and Tufts, 2018;Couth et al, 2020). Table 3 shows a summary of studies that investigated the effect of noise exposure on ABR wave I amplitude in humans.…”
Section: Human Studiesmentioning
confidence: 99%
“…After controlling for audiometric threshold loss, ABR wave I amplitude was found to decrease by about 17.8% per decade. Buran et al ( 2022 ) provided a re-analysis of the Bramhall et al ( 2017 ) data ( n = 64; age range: 19–35; summarized in Table 3 ). After the potential confounds of sex and OHC function (as reflected by distortion product otoacoustic emission levels) were accounted for, ABR wave I amplitude measured at 110 dB peSPL was found to decrease by about 6.1% per decade.…”
Section: Objective Proxy Measures Of Cochlear Synaptopathymentioning
confidence: 99%
See 1 more Smart Citation
“…Listeners with higher degrees of CS (and hence smaller unprocessed EFR markers) may be those who benefitted less from CS-compensating processing, however this was not clear from the results of our statistical analysis. To this end, diagnostic assessments of the individual degree of CS in each participant [58, 59] could help to explain the individual performance differences between participants with more certainty.…”
Section: Discussionmentioning
confidence: 99%
“…These markers included envelope-following responses (EFRs), amplitude-modulation (AM) detection sensitivity, and SI in terms of speech reception thresholds (SRTs) and word recognitions scores (WRSs). Because a direct quantification of CS relies on post-mortem imaging of the temporal bone [7, 57], we focussed on older listeners who had been shown to be affected by CS through non-invasive electroencephalographic (EEG) techniques [14, 58, 59].…”
Section: Introductionmentioning
confidence: 99%